The Determinants of Bank Profitability in China under Global Financial Crisis - Wang, Wei (2018)
Abstract The purpose of this study is to explore bank-specific, industry-specific characteristics and macroeconomic factors affecting bank profitability from 2013 and 2017, during which, the banking sector was still influence by post crisis and the strong governance. The analysis highlights the links between bank profitability and policies made more recently like the stimulus package in Global Financial Crisis left a large volume of non-performing loans. The empirical method applied is Two-Step System GMM. Both ROAA and ROAE are used to measure the dependent variable, although the results suggests that ROAA is more suitable in Chinese case. All relationship of variables and bank profitability are in line with expectation. As for bank-specific ones like cost to income, impaired loan to gross loan, interest income to total assets, Z SCORE, equity to total assets and logarithm of total assets are found significant. The study presents the evidence that the larger size of bank may produce less profit. Concerning the industry and macroeconomic variables, the evidence is highly significant. Banks generate more profits in an upward economic condition. While, variables like loan loss reserves to total assets and tax to tax before profit are found no impact on ROAA and ROAE.